The influence of initial stresses on energy release rate and total electro-mechanical potential energy for penny-shaped interface cracks in PZT/Elastic/PZT sandwich circular plate-disc - Akbarov, Surkay D.; Cafarova, Fazile, I; Yahnioglu, Nazmiye (TECHNO-PRESS, 2018)
This paper studies the energies and energy release rate (ERR) for the initially rotationally symmetric compressed (or stretched) in the inward (outward) radial direction of the PZT/Elastic/PZT sandwich circular plate with interface penny-shaped cracks. The investigations are made by utilizing the so-called three-dimensional linearized field equations and relations of electro-elasticity for piezoelectric materials. The quantities related to the initial stress state are determined within the scope of the classical linear theory of piezoelectricity. Mathematical formulation of the corresponding problem and determination of the quantities related to the stress-strain state which appear as a result of the action of the uniformly normal additional opening forces acting on the penny-shaped crack's edges are made within the scope of the aforementioned three-dimensional linearized field equations solution which is obtained with the use of the FEM modelling. Numerical results of the energies and ERR and the influence of the problem parameters on these quantities are presented and discussed for the PZT- 5H/Al/PZT-5H, PZT-4/Al/PZT-4, BaTiO3/Al/BaTiO3 and PZT-5H/StPZT-5H sandwich plates. In particular, it is established that the magnitude of the influence of the piezoelectricity and initial loading on the ERR increases with crack radius length.
Keywords: electro-mechanical energy; energy release rate; piezoelectric material; penny-shaped interface crack; sandwich circular plate; ELASTIC CORE LAYERS; PIEZOELECTRIC MATERIALS; BUCKLING DELAMINATION; BOUNDARY-CONDITIONS; FRACTURE; STRIP; FACE; MECHANICS; TIPS; Engineering; Instruments & Instrumentation